The Education Policy of the European Union - Želvys, Rimantas (Acta Paedagogica Vilnensia, 1997)
In the early stages of European integration, an education policy had not been identified as a political area for joint actions of the Member States. The first initiatives with regard to education by the European Communities of sizable political impact were undertaken in 1976. In December 1991, the Maastricht Treaty of the European Union finally laid the grounds for a legitimate role to be played by the EC Commission in the field of education. European Cummnity does not regulate the content of teaching and the organization of education systems of the Member States. The education policy of the European Union at present is mainly implemented through a series of programmes concerned with education and training. It is interesting to note that, while Member States of the Community are fiercely defending their own right to establish a content and methods of national education, the Community is recommending quite a different approach to the countries of Central and Eastern Europe. As a result, people in Central and Eastern Europe are starting to feel that the transfer of knowledge, experience, and paradigms, which takes place, on the whole, rather uncritically, threatens their cultural identity. Nevertheless, we should not underestimate the substantial positive impact of the programmes providing assistance to newly developing democracies, which were established by the Community after the fall of the Communist regimes in 1989 and 1990.